2020
DOI: 10.1007/s00170-020-05357-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the different variants of the surface treatment on the durability of forging dies made of Unimax steel

Abstract: The study performs an analysis as well as makes a comparison of the durability of forging tools used in the die forging process made of high-strength steel Unimax. For tool steel WCL (1.2343 according to DIN), which has been applied so far, the obtained average durability has been at the level of about 6000 forgings. Additionally, in order to increase the durability of the Unimax material, two surface treatment variants were applied: in the form of ion nitriding (for nitrides A) and gas nitriding together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Following the research, it was found that the trimming dies made of K360 steel showed the highest durability. This confirms that a large amount of alloying elements, present in the chemical composition of this steel, but also a high hardness of 65 HRC, obtained after heat treatment hardening, are factors that can contribute to increasing the durability of trimming dies [20,21]. However, certain areas with cracks have been observed on the active surfaces of the trimming dies (Figure 5), which shows that this steel is very sensitive to mechanical shocks and is not very suitable to be used to make this type of trimming dies.…”
Section: Analysis Of the Durability Of Trimming Dies Made Of Differen...supporting
confidence: 64%
“…Following the research, it was found that the trimming dies made of K360 steel showed the highest durability. This confirms that a large amount of alloying elements, present in the chemical composition of this steel, but also a high hardness of 65 HRC, obtained after heat treatment hardening, are factors that can contribute to increasing the durability of trimming dies [20,21]. However, certain areas with cracks have been observed on the active surfaces of the trimming dies (Figure 5), which shows that this steel is very sensitive to mechanical shocks and is not very suitable to be used to make this type of trimming dies.…”
Section: Analysis Of the Durability Of Trimming Dies Made Of Differen...supporting
confidence: 64%
“…Cena kalupa je oko 30[%] ukupnih troškova za postupak kovanja u zatvorenim kalupima. Prema tome, povećanje radnog veka kalupa za 100[%] može smanjiti ukupne troškove za oko 15[%] [83][84][85][86][87]. U svetlu ovoga, povećanje izdržljivosti alata je kritičan izazov u proizvodnji otkovaka.…”
Section: Plazma Nitriranje U Funkciji Poboljšanjaunclassified
“…c After the machining operation [166] Fig. 25 Defects in dies and moulds that could be repaired by employing hybrid AM solutions [169,170] linear gradient between Fe and Ni was achieved as a result of the good diffusion and the strong bonding between the deposited layers.…”
Section: Functionally Graded Materialsmentioning
confidence: 99%